(untitled) (Anuário Antropológico, 2023)
Two decades have passed since indigenous peoples began to have access to higher education in Brazil, and about fifteen years since the first indigenous anthropologists graduated. This is a short time, considering the weight of over five centuries of colonization. However, indigenous scholars trained in universities have already produced some essays on their first theoretical, methodological, and political findings in anthropology. Due to the substantial increase of indigenous professionals, we now live in rich, effervescent and promising times regarding future accomplishments, despite the many challenges, doubts and reservations.